Physico-chemical properties of chickpea flour obtained using roller milling and extrusion pre-cooking - Martin, Randall Clade (Kansas State University, 2020)
Chickpea is a high protein pulse that is gaining popularity in U.S. and international markets. This research focused on an integrated approach to process raw chickpeas grain into precooked chickpea flour with improved functionality and flavor for downstream applications such as baked products. This was achieved by conducting bench-top milling and extrusion studies, followed by scaling-up to pilot milling and extrusion, and physico-chemical characterization of the flour and evaluation of its functionality in baked cracker applications. The approach involved processing techniques, such as roller milling and extrusion, which are not typically used for pre-cooked chickpea flour but have the potential of improving efficiency and quality. The first chapter of this thesis covers the bench-top milling and extrusion trials as a proof of concept at a smaller scales. The second chapter describes the pilot-scale roller milling process and evaluation of milling efficiency. The third and final chapter covers the pilot-scale extrusion process and evaluation of the resultant pre-cooked flour, including physical and sensory properties of crackers baked using the flour. Two varieties of chickpea were evaluated, Kabuli and Desi. Raw ‘Kabuli’ chickpeas were obtained as whole seeds, while ‘Desi’ chickpeas were obtained as split and de-hulled seeds. Benchtop roller mills were used to mill the chickpeas to a coarse meal and a fine flour. A benchtop extrusion trial was conducted using the chickpea meal and flour. The extruded product was reground into a precooked flour that was evaluated for physico-chemical properties and baked into crackers for physical and sensory testing. The benchtop milling information was used for scaling-up to a pilot flour mill. Again, the chickpeas were milled to a coarse meal and fine flour, and a flow sheet was developed. The chickpea meal obtained for each variety was then extruded on a pilot-scale twin-screw extruder under varying in-barrel moistures to obtain three distinct processing intensities. The extruded product was reground to flour and evaluated for physico-chemical properties and functionality in baked cracker application. The results of this research include four bench-top and two pilot-scale milling flow sheets for processing the two varieties of chickpeas into coarse meal and fine flour using roller mills and found that whole Kabuli seeds mill more efficiently than split Desi seeds (+9.3%). The bench-top data translated extremely well to pilot-scale, which showed the benefits of small-scale milling and extrusion research before scale-up. The extrusion pre-cooking resulted in enhanced flour functionality (final viscosity increased 500-1500cP) than commercial samples. Dough made with precooked flour sheeted easier than those made with raw flour. Crackers baked using pre-cooked flour also had a reduced hardness in comparison to raw flour (>400g). Pre-cooking resulted in a significantly lower gritty texture. Beany flavor of the crackers was not significantly reduced but the cooking process did not increase any rancid or negative flavors. This research provides the food industry with novel value-added milling and extrusion processing techniques for chickpeas flour for improving efficiency and functionality.
Keywords: Chickpea; Extrusion; Milling; Baking; Sensory